2012
DOI: 10.35808/ersj/374
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renewable Energy Sources on Economic Growth and CO2 Emissions - a SVAR approach

Abstract: We analyze how an increasing share of Renewable Energy Sources on Electricity generation (RES-E) affects Gross Domestic Product (GDP) and Carbon Dioxide (CO2) emissions using a 3 variable Structural Vector Autoregressive (SVAR) methodology. We used a sample of four countries with different levels of economic development and social and economic structures but a common effort of investment in RES in the last decades. The period considered was 1960 to 2004. The existence of unit roots was tested to infer the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 49 publications
8
56
0
2
Order By: Relevance
“…This result is in line with a priori expectations. This outcome is also consistent with the literature on the relationship between economic growth and RE consumption [Apergis, Payne, 2014Silva et al, 2012;Sadorsky, 2011].…”
Section: Variance Decompositionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result is in line with a priori expectations. This outcome is also consistent with the literature on the relationship between economic growth and RE consumption [Apergis, Payne, 2014Silva et al, 2012;Sadorsky, 2011].…”
Section: Variance Decompositionsupporting
confidence: 91%
“…He pointed out that increases in income and CO2 emissions are the major drivers for increases in RE consumption in the long run. Silva et al [Silva et al, 2012] analyzed how an increasing share of RE sources in power generation affects economic growth and carbon emissions using structural VAR approach over the period 1960 to 2004 for Denmark, Portugal, Spain, and the United States. Their findings show that economic costs emerged with the increase of RE in terms of GDP per capita and the decrease of CO2 emissions per capita was ensured.…”
Section: Review Of the Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, Magazzino [16] has shown that the energy sector has negligible effects on GHG emissions. Silva et al [21] and Maslyuk and Dharmarathna [22] have found that renewable energy shares in electricity generation increase GHG emissions; in contrast, Shabbir et al [23] and Yu and Kim [24] have concluded that the rise in renewable energy consumption could decrease GHG emission levels by substituting non-renewable energy. However, Menyah and Wolde-Rufael [13] and Tiwari [14] have shown that renewable energy consumption could not contribute to the reduction of GHG emissions.…”
Section: Introductionmentioning
confidence: 99%